Phosphorus Mobilization in Plant–Soil Environments and Inspired Strategies for Managing Phosphorus: A Review - Muhammad Ibrahim; Muhammad Iqbal; Yu-Ting Tang; Sardar Khan; Dong-Xing Guan; Gang Li (Agronomy, 2022)
Crop productivity and yield are adversely affected by the deficiency of P in agricultural soil. Phosphate fertilizers are used at a large scale to improve crop yields globally. With the rapid increase in human population, food demands are also increasing. To see that crop yields meet demands, farmers have continuously added phosphate fertilizers to their arable fields. As the primary source of inorganic phosphorous, rock phosphate is finite and the risk of its being jeopardized in the foreseeable future is high. Therefore, there is a dire need to improve plant-available P in soil, using feasible, environmentally friendly technologies developed on the basis of further understanding of P dynamics between soil and plants. This study systemically reviews the mechanism of P uptake and P-use efficiency by plants under starvation conditions. The recent advances in various strategies, especially imaging techniques, over the period 2012–2021 for the measurement of plant-available P are identified. The study then examines how plants fulfill P requirements from tissue-stored P during P starvation. Following this understanding, various strategies for increasing plant-available P in agricultural soil are evaluated. Finally, an update on novel carriers used to improve the P content of agricultural soil is provided.